Asimilasi sebagai Terjemahan Bentuk Adaptasi dalam Resiliensi Komunitas Kampung Kota di Kampung Sudiroprajan Surakarta - Tendra Istanabi; Muhammad Sani Roychansyah; Deva Fosterharoldas Swasto (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2018)
Resilience is a concept that integrates between mitigation, adaptation and innovation. On a smaller scale, community-based resilience forms a translation of strong social capital. In Indonesia the majority of the urban community is formed in a container called Kampung Kota. Kampung Kota has the character of tolerance, cohesiveness, and solidarity. Kampung Kota becomes important to be used as research setting because with its characteristic, Kampung Kota able to produce its own value so that it can face threat, pressure and turmoil with its way. Kampung Sudiroprajan is one of the kampung Kota in Surakarta City that has unique resilience experience especially related to the relationship between Javanese and Chinese. This study aims to determine the concept of resilience that is formed in Kampung Sudiroprajan as part of the Kampung Kota community. Kampung Sudiroprajan can give an idea of resilience concept of community scale which tend to original and typical. This research uses case study methodology by exploring the form of resilience conducted in Kampung Sudiroprajan. This study found the uniqueness of adaptation process of Kampung Sudiroprajan community. Adaptation is translated in the form of assimilation. The assimilation resulted in the social condition of the society which tends to be more fluid, especially in the face of several times the events that become threats, pressure, and turmoil for the Chinese. Assimilation creates a new value that becomes the glue of the relationship for the Javanese Ethnic community and the Chinese Ethnic Community.